Muslim Khilafah Conference held in Wembley Arena, 7 August 1994 - The International Muslim Khalifah Conference (1994 : Wembley Arena) (London : Al-Khilafah Publications, 1994)
The conference concentrated upon raising awareness for the call to re-establish the khilafah (Islamic state) and the declaration made at the end of the conference placed the work for re-establishing the khilafah in the Muslim world as the number one priority for all Muslims, and a necessity for all the latter day tragedies facing Muslims including: Palestine, Bosnia and Kashmir to name but a few.
Copy available in DVD format
Speakers: Abdullah Kapich (Bosnia), Abdullah Ramadhan (Turkey), Israr Ahmed (Pakistan), Abu Talha (Ash Sham), Mohammed Hanini (USA), Jamal Harwood (Britain), Omar Bakri Mohammed (Ash-Sham), Farid Kassim
Keywords: Islamic countries